1994
DOI: 10.1021/bc00027a003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hapten binding to immunoconjugates by electrospray ionization mass spectrometry

Abstract: Electrospray ionization mass spectrometry (ESI-MS) has been used to characterize the covalent binding of different haptens to the enzyme glucose 6-phosphate dehydrogenase. The technique allows one to directly observe the relative amounts of each conjugated species present in a mixture, as well as the average hapten number. These measurements are useful for optimizing reaction conditions to yield a more precisely defined product for use in immunoassays. The results obtained show that ESI-MS with a quadrupole an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
(17 reference statements)
0
6
0
1
Order By: Relevance
“…Thus, ESI-MS is becoming a common tool for molecular weight determination of proteins, DNA/RNA (20)(21)(22), peptides, and other macromolecules. However, there have been limited reports on characterization of conjugates using ESI-MS. A recent report detailed the characterization of haptenenzyme conjugates and concluded that for proteins in the mass range of 55 kDa, only conjugates with a hapten density of eight or less could be analyzed (23).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ESI-MS is becoming a common tool for molecular weight determination of proteins, DNA/RNA (20)(21)(22), peptides, and other macromolecules. However, there have been limited reports on characterization of conjugates using ESI-MS. A recent report detailed the characterization of haptenenzyme conjugates and concluded that for proteins in the mass range of 55 kDa, only conjugates with a hapten density of eight or less could be analyzed (23).…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique is not advocated for photochemical coupling due to non specific (“dark”) labeling or photodeiodination ( , ). Mass spectrometry, particularly electrospray and matrix-assisted laser desorption ionization techniques, have become increasingly useful for the characterization of conjugates which are soluble at sufficient (approximate micromolar) concentration ( ).…”
Section: Resultsmentioning
confidence: 99%
“…Normalmente, para se obter uma boa produção de anticorpos, são necessários entre 10 e 30 grupos haptênicos por cada 100 KDa de proteína 32 , apesar de já terem sido obtidos resultados satisfatórios com relações mais altas ou mais baixas. Existem vários procedimentos -geralmente por espectrometria UV-vis -para se estimar quantitativamente o número de conjugados de hapteno unidos à proteína [33][34][35] , embora nos últimos anos tenham surgido outros métodos, como dessorção da matriz por meio de laser-espectrometria de massas (MALDI-MS) e a ionização "electrospray"-espectrometria de massas (ESI-MS) [36][37][38] .…”
Section: Preparação Dos Imunógenosunclassified